2016
DOI: 10.5812/iranjradiol.34220
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of Three Cone Beam Computerized Tomography Scanners at Different Fields of View in Terms of Various Head and Neck Organs

Abstract: BackgroundMarketing new radiography devices necessitates documenting their absorbed X-ray doses. Since the current literature lacks studies on new devices, we assessed the doses of two new devices that had not previously been assessed.ObjectivesThe new devices were compared to the Promax three dimensional (3D) scanner at two fields of view (FOV) in nine critical head and neck tissues and organs.Materials and MethodsSeventeen thermoluminescence dosimeters positioned in an average-sized male RANDO phantom were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Several parameters can be varied during image acquisition according to the diagnostic task but still no protocols have been established for specific diagnostic tasks in dentistry [18] . In our study we proved that changing the voxel size will not affect the accuracy of the nerve tracing tool, and so using larger voxel size will not affect the clinical outcome and decrease the patient absorbed dose according to Nikneshan et al [36] .…”
Section: Discussionsupporting
confidence: 58%
“…Several parameters can be varied during image acquisition according to the diagnostic task but still no protocols have been established for specific diagnostic tasks in dentistry [18] . In our study we proved that changing the voxel size will not affect the accuracy of the nerve tracing tool, and so using larger voxel size will not affect the clinical outcome and decrease the patient absorbed dose according to Nikneshan et al [36] .…”
Section: Discussionsupporting
confidence: 58%
“…The findings indicated that dental CBCT delivers lower doses for orthognathic patients, whereas CBCT and MDCT give equivalent doses for temporal bone operations. In 4, Sima Nikneshan et al [52] estimated average tissue absorbed dose and effective dose using TLD chips in a radiation analog dosimetry phantom in Comparative dosimetry of dental CBCT systems for important organs. The average absorbed dosage in both FOVs varied from 0.31 mGy to 81.42 mGy.…”
Section: Resultsmentioning
confidence: 99%
“…These findings highlight the optimal efficacy of indirect dosimetry by use of a software program as an alternative for other dosimetry method. Nikneshan et al (11) , performed dosimetry for three CBCT devices with small and large FOVs using TLD and RANDO phantom. The organ absorbed dose and whole-body effective dose in smaller FOVs were higher, probably due to automatic increase in image resolution by changing the size of FOV from large to small (11) .…”
Section: Discussionmentioning
confidence: 99%